2020
DOI: 10.5194/hess-24-977-2020
|View full text |Cite
|
Sign up to set email alerts
|

Controls of fluorescent tracer retention by soils and sediments

Abstract: Abstract. Fluorescent dyes like uranine (UR) and sulforhodamine B (SRB) have been used for decades as artificial tracers in hydrological studies. Recently, attempts have been made to trace organic pollutants in soil with such dyes, but the knowledge of the controls of sorption of UR and SRB in soils is still incomplete and poorly standardised. For this reason, we selectively controlled clay, organic matter (OM) and pH within batch experiments and quantified systematically the impact and possible interactions o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…is the molecular weight of the adsorbate, c ref [mol m −3 ] is a reference concentration used for units correction, and (dimensionless) is the isotherm exponent. K d and depend on factors such as the type of adsorbent and adsorbate, temperature, and pH, among others (Skopp 2009;Bork et al 2020). Previous studies (Brownawell et al 1997;John et al 2000;Botella-Espeso et al 2021) proved that the Freundlich isotherm (with different K d and values) is the most suitable isotherm for reproducing adsorption of surfactants in soils, specially for the case of non-ionic surfactants.…”
Section: Transport and Adsorption Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…is the molecular weight of the adsorbate, c ref [mol m −3 ] is a reference concentration used for units correction, and (dimensionless) is the isotherm exponent. K d and depend on factors such as the type of adsorbent and adsorbate, temperature, and pH, among others (Skopp 2009;Bork et al 2020). Previous studies (Brownawell et al 1997;John et al 2000;Botella-Espeso et al 2021) proved that the Freundlich isotherm (with different K d and values) is the most suitable isotherm for reproducing adsorption of surfactants in soils, specially for the case of non-ionic surfactants.…”
Section: Transport and Adsorption Modelingmentioning
confidence: 99%
“…Surfactants can be further affected by other processes such as degradation caused by light or microorganisms, which deplete their environmental concentration (Bork et al 2020). A general overestimation of adsorption from laboratory batch experiments when compared with field scale experiments, i.e., infiltration experiments, has also been observed (Botella-Espeso et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the high discrepancy between the retention of conservative tracers ( , ) and UR at F.3 revealed that UR ought to be considered as a non-conservative tracer with respect to its sorption properties. This was described previously for UR application in soils with comparable OC content, texture and pH 44 , 61 , 62 .
Figure 2 Breakthrough curves (BTCs) of the tracers bromide, chloride, UR, SRB and the biocides diuron, terbutryn, OIT and the sum of biocides (diuron+terbutryn+OIT; represented by diamonds).
…”
Section: Resultsmentioning
confidence: 99%
“…At this temperature OC had been transformed to 91 . Additionally, sorption isotherms for UR and SRB were produced according to OECD guideline 106 92 described in 62 and linear sorption coeffients ( -values) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Estudos acerca dos mecanismos de controle de adsorção de uranina em sedimentos ainda são incompletos e pouco sistematizados (BORK et al, 2020). Portanto, a avaliação de possíveis interações físicas entre o traçador e o material sólido pelo qual ele percolará deve, preferencialmente, preceder sua apli-cação no aquífero, de modo a antever possíveis perdas de massa.…”
Section: Artigosunclassified